2020
DOI: 10.20469/ijbas.6.10003-1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Diversification Strategies and Operational Capabilities on Financial Performance in Thai Professional Service Firms

Abstract: The professional service sector plays a crucial role in the world economy, especially in emerging countries. This research explores the impact of diversification strategies and operational capabilities on financial performance in Thai professional firms. Financial data of 96 companies in the service sector listed on the Stock Exchange of Thailand (SET) was collected. Partial Least Squares (PLS) regression was selected as an analysis method. The results find that service diversification strategy, but not intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…The results highlighted that operational capabilities not only influence the SMEs’ performance but act as a mediator between MO and SMEs performance, and SC orientation and SMEs performance. Thirathon and Meeprom (2020) also found that operational capabilities can help firms in increasing their performance. Thus, H8, H10, and H12 are accepted.…”
Section: Discussionmentioning
confidence: 97%
“…The results highlighted that operational capabilities not only influence the SMEs’ performance but act as a mediator between MO and SMEs performance, and SC orientation and SMEs performance. Thirathon and Meeprom (2020) also found that operational capabilities can help firms in increasing their performance. Thus, H8, H10, and H12 are accepted.…”
Section: Discussionmentioning
confidence: 97%
“…According to Thirathon and Meeprom (2020), operational capabilities comprise of processes, aptitudes and routines specific at each unit of business and have been developed with operation management system and regularly applied in solving problems through configuring more resources. Bleady and Bleady (2018) further views operational capability as an integration of composite set of tasks executed by a firm aiming at enhancing its output level through application of the most efficient and effective production capabilities, material flow and technology.…”
Section: Operational Adjustment Capabilitymentioning
confidence: 99%
“…Portfolio diversification is the process of combining various assets aiming at reducing the general risk related with the entire organizational portfolio referred to as unsystematic risk (Thirathon & Meeprom, 2020). A well-mixed portfolio attained on different types of investments bears the capabilities of yielding high returns with reduced risks compared to individual investment thus creating a positive financial impact, performance and stability.…”
Section: Background Of the Studymentioning
confidence: 99%
“…A portfolio return solely depends on the risk and in order to minimize the risks accompanying individual asset portfolio, micro finance institutions opts for diversification. In the diversification, portfolio assets are mixed with the portfolio aiming at maximizing returns while minimizing risks (Thirathon & Meeprom, 2020). The risk premium however varies from nation to nation and is particularly high in developing and emerging markets due to risk and volatility attached to such markets.…”
Section: Background Of the Studymentioning
confidence: 99%